Corporate Funding and Sustainability of Non- Governmental Organizations in Africa - Abdullahi, Danjuma; Baba, Yahaya T.K (Games Review, 2016)
The role of NGOs in development cannot be over emphasized, previous studies only discussed on the NGO’s roles in development without much emphasis on their sustainability. Thus, this study focuses on corporate funding and sustainability of NGOs in Africa. Qualitative research was used, 19 informants were interviewed. The result shows that NGOs in third world face many problems, ranging from funding, lack of time, poverty, illiteracy and lack of mobilization contributed to limited activities of NGOs in third world. The paper recommends increase in participation, investment in education and creation of awareness.